The Relevance of Scuba Diving Activities as A Tourist Attraction on Pangkor Island - Mohamad Pirdaus Yusoh; Nurhazliyana Hanafi; Normah Abdul Latip; Jeannet Steaphen; Muhammad Fuad Abdullah; Ang, Kean Hua (Malaysia Institute of Planners, 2023)
Scuba diving tourism is one of the tourism products that contributes to Malaysia's economic returns. There are three main issues underlying this research problem, namely the validity of Pangkor Island as a scuba diving tourism destination in Malaysia, the confusion about Pangkor Island's actual status as a scuba diving tourism destination in Malaysia based on tourism agency promotions and souvenir sales, and past studies conducted by local scholars. To obtain validity, several stakeholders were made respondents of the study, namely foreign tourists, local residents, and resort entrepreneurs. This study aims to identify the characteristics of tourist attractions on Pangkor Island based on the perceptions of foreign tourists and local communities, examine the involvement of local communities in tourism development, and the level of their knowledge about scuba diving tourism. Furthermore, it examines whether this activity is a characteristic attraction that drives international tourists to visit Pangkor Island based on the stated attraction characteristics and the scuba diving activity service offerings by hotel and resort entrepreneurs there. This study uses a quantitative approach and is supported by a qualitative approach. The research methods used are face-to-face interviews using questionnaires, observations, and in-depth interviews. The study's findings on 125 foreign tourists, 179 local communities, and 42 hotels and resorts show that Pangkor Island is not relevant as a scuba diving destination. All three stakeholders gave negative responses to this research problem. For foreign tourists, the main attraction stated is the beach and the sea, as well as the attractive natural environment, which is 71.4%. Local community interviews showed that Pangkor Island is not popular as a scuba diving destination, which is 52.0%, and resort analysis found that scuba diving package offerings are only offered by four out of 42 resorts and hotels on the island, and only if there is demand. The study's findings indicate that scuba diving is not popular as a tourist attraction there. Therefore, this study's findings reject the Professional Association of Diving Instructors (PADI) statement that places Pangkor Island as a scuba diving tourism destination. In conclusion, this research contributes to the academic discipline, particularly in service geography and tourism, and policy makers such as the Malaysian Ministry of Tourism.